2013
DOI: 10.1016/j.neuron.2013.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity between Amygdala and Cingulate Cortex for Adaptive Aversive Learning

Abstract: The ability to switch flexibly between aversive and neutral behaviors based on predictive cues relies on learning driven by surprise or errors in outcome prediction. Surprise can occur as absolute value of the error (unsigned error) or its direction (signed errors; positive when something unexpected is delivered and negative when something expected is omitted). Signed and unsigned errors coexist in the brain and were associated with different systems, but how they interact and form across large networks remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
90
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 70 publications
15
90
0
Order By: Relevance
“…BLA neurons are sensitive to fear prediction error in vitro (Bauer et al, 2001) and in vivo (Paton et al, 2006;Belova et al, 2007Belova et al, , 2008Johansen et al, 2010), and similar findings have been reported in human neuroimaging studies (Dunsmoor et al, 2008). Of greatest relevance, there is bidirectional fear prediction error signaling between primate dorsal ACC (dACC) and amygdala (Klavir et al, 2013), and prediction error-related BOLD signals in human dACC precede changes in the amygdala BOLD signal during learning (Eippert et al, 2012). Thus, it is likely that dmPFC-BLA interactions contribute to the restoration of prediction error and fear learning observed here.…”
Section: Methodological Considerationsmentioning
confidence: 66%
“…BLA neurons are sensitive to fear prediction error in vitro (Bauer et al, 2001) and in vivo (Paton et al, 2006;Belova et al, 2007Belova et al, , 2008Johansen et al, 2010), and similar findings have been reported in human neuroimaging studies (Dunsmoor et al, 2008). Of greatest relevance, there is bidirectional fear prediction error signaling between primate dorsal ACC (dACC) and amygdala (Klavir et al, 2013), and prediction error-related BOLD signals in human dACC precede changes in the amygdala BOLD signal during learning (Eippert et al, 2012). Thus, it is likely that dmPFC-BLA interactions contribute to the restoration of prediction error and fear learning observed here.…”
Section: Methodological Considerationsmentioning
confidence: 66%
“…The inhibition of US processing could occur either directly in the PAG, through activation of a descending analgesia circuit that inhibits pain processing at the level of the spinal cord, and/or through refinement of US processing at various stages of the circuit. Possibly related to this, other recent work suggested that the ACC may be important in refining prediction error coding in the amygdala during learning 68,79 , although how ACC neurons contribute to this process is not clear. Given that aversive US-evoked activity in LAn neurons is important for triggering fear learning 54,55,80 , the CEn-PAG circuit mechanism could set the amount of learning that occurs at a given US intensity (that is, the learning asymptote) by regulating the amount of LAn neuronal depolarization evoked by the US during training.…”
Section: Encoding Of Aversive Instructive Signals In the Fear Circuitmentioning
confidence: 92%
“…By recording from LAn and BAn neurons, a number of studies found that cells in these regions exhibit firing responses proportional to prediction error 14,[67][68][69] . Thus, neurons in these regions respond robustly to unpredicted aversive USs, but less when the US is predicted by a well-trained auditory CS after learning (Fig.…”
Section: Encoding Of Aversive Instructive Signals In the Fear Circuitmentioning
confidence: 99%
“…The amygdala is an important component of the medial temporal lobe and plays an important role in the relationship between emotion and cognition (Pessoa, 2008;Pessoa and Adolphs, 2010). Moreover, the amygdala exhibits widespread connectivity with cortical regions, such as the parietal lobe, orbitofrontal cortex, ventromedial prefrontal cortex, middle temporal gyrus (MTG), inferior temporal gyrus, cingulate, thalamus, insula, and hippocampus (Klavir et al, 2013;Pessoa, 2008;Pessoa and Adolphs, 2010;Roy et al, 2009;Xie et al, 2012;Yao et al, 2013). The amygdala is also thought to be an important connection hub in the brain network (Pessoa, 2008;Tomasi and Volkow, 2011).…”
Section: Introductionmentioning
confidence: 99%